The Street-Smart Side of Business : A Behind-The-Scenes Guide to Inspire Forward Thinking. - Acosta, Tara. (New York : Business Expert Press, 2021)
This book provides realistic insight as to what running a business is really about. It will help prepare you for all aspects of business and teach you how to protect yourself and your investment. The simplicity of using our intuition is often overlooked. The point is to understand exactly what you're getting into and not be blinded by the appearance of a good opportunity. This book will open your eyes and show you how to evaluate opportunities, people, and motives-skills often overlooked but are critical aspects of owning and operating a successful business. Prepare to get in tune with your "street smarts" in order to be successful in business and in life.
Cover -- Halftitle -- Title -- Copyright -- Dedication -- Description -- Contents -- Introduction -- Chapter 1: Pick Your Poison -- Chapter 2: Burst Your Bubble -- Chapter 3: What's the Plan, Stan? -- Chapter 4: Cribs -- Chapter 5: Wise Guys -- Chapter 6: Hangry for Business -- Chapter 7: Rooted -- Chapter 8: Can You Hack It? -- Chapter 9: A Wolf in Sheep's Clothing -- Chapter 10: Loyal Till the End -- Chapter 11: Mentorship -- Chapter 12: The Big Mahoff -- Chapter 13: Kingpin -- Chapter 14: Promoting Your Business -- Chapter 15: It's Not What You Know… -- Chapter 16: Underdog -- Chapter 17: The Gamble -- Chapter 18: Risky Business -- Chapter 19: Choose Your Yuppy -- Chapter 20: Client Connections -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Success in business; Business planning; Entrepreneurship; Electronic books